Educational Media and Technology Yearbook Volume 34, 2009 - Orey, Michael; McClendon, V. J.; Branch, Robert Maribe (Educational Media and Technology Yearbook ;, 2009)
The Educational Media and Technology Yearbook is dedicated to theoretical, empirical and practical approaches to educational media development. All chapters are invited and selected based on a variety of strategies to determine current trends and issues in the field. The 2009 edition will highlight innovative Trends and Issues in Learning Design and Technology, Trends and Issues in Information and Library Science, and features a section that lists and describes Media Related Organizations and Associations in North America. The Educational Media and Technology Yearbook, a scholarly resource for a highly specialized professional community, is an official publication of the AECT and has been published annually for 33 years.